Effect of Air Contaminants on Poultry Immunological and Production Performance - Almuhanna, E.A.; Ahmed, A.S.; Al-Yousif, Y.M. (International Journal of Poultry Science, 2011)
The concentration and particle size distribution of airborne particles and toxic gases in two commercial poultry houses were measured and analyzed. This field study was conducted at Al-Ahsa of Saudi Arabia in order to characterize air contaminants in the mechanically ventilated poultry houses under the climatic conditions of Saudi Arabia. In the mechanically ventilated poultry houses (M.V.), the mean Total Suspended Particle concentration (TSP) was 4.25 and 3.64 mg/m3, respectively, the PM10 concentration (particulate matter with a diameter less than or equal to 10 μm) was 2.26 and 1.79 mg/m3, respectively and the PM2.5 concentration (particulate matter with a diameter less than or equal to 2.5 μm) was 0.08 and 0.07 mg/m3 respectively. The TSP values were greater than the suggested threshold values for indoor air contaminants in livestock buildings; however, the PM2.5 values of both houses did not exceed the suggested threshold values for indoor air contaminants in livestock buildings. The Geometric Mean Diameter (GMD) based on the mass concentration of particles in both houses was 8.45 and 8.31 μm, respectively. The concentration of NH3, CO2, SO2, NO2 and H2S was measured and the results indicated that ammonia was the dominant gas in both houses. Moreover, the majority of gases did not exceed the threshold values. At the M.V. poultry house, the concentration of airborne particles and toxic gases was strongly affected by the barn ventilation rate. The current results suggested that the increase of air contaminants and gases negatively affect the general productive performance and immune response under commercial conditions.